Analysing software quality using cmmi-2 with agile-scrum framework - Chaitanya Krishna, B; Yeshwanth Srinath, A; Bhavani, N; Jaya Sai, G (International Journal of Engineering and Technology, 2017)
Capability Maturity Model Integration is the best proposed theory for software quality assurance. Implementing the agile methods linking to Capability Maturity Model Integration and presenting the software. Basically Scrum is one of the best implemented methods. We will link the scrum to CMMI level managed to the scrum methods and define software quality.This Application totally involves with Consumer or customer behaviour while shopping an Item.Seller Companies analyzes this behaviour in order to rate their product or increase the sales of the product. Every Product selling company need to know about market analysis of their product. This project is proposed to provide market analysis of the each product to the seller companies with interaction of the customer purchases. Now days because of increase in media and internet, shopping items through online is increased. Seller companies need to rank their products and they need to administrate products in their companies , that is few products they want to retain, few they have delete/stopbut in order to stop or promote a product they need to know about product status in the market. With survey sites sometimes it may fake results. To overcome such kind of drawbacks, this project is proposed, this project directly estimates the behaviour of customer, in search, and buy a product. The result given this project is useful for company to estimate the status of the project in the market.